2021
DOI: 10.1155/2021/2514947
|View full text |Cite
|
Sign up to set email alerts
|

miRNA‐27a Transcription Activated by c‐Fos Regulates Myocardial Ischemia‐Reperfusion Injury by Targeting ATAD3a

Abstract: MicroRNA-27a (miR-27a) has been implicated in myocardial ischemia-reperfusion injury (MIRI), but the underlying mechanism is not well understood. This study is aimed at determining the role of miR-27a in MIRI and at investigating upstream molecules that regulate miR-27a expression and its downstream target genes. miR-27a expression was significantly upregulated in myocardia exposed to ischemia/reperfusion (I/R) and cardiomyocytes exposed to hypoxia/reoxygenation (H/R). c-Fos could regulate miR-27a expression b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Specifically, MyoD binds to and activates the miR‐27a‐3p promoter, with binding sites located within the core promoter region (−234/−165 bp) (Tao et al., 2022). Furthermore, c‐Fos was found to promote miR‐27a expression by specifically binding to the miR‐27a promoter region (−983 to −974 region) and subsequently leading to enhance ischemia/reperfusion‐induced myocardial apoptosis in vitro (Bao et al., 2021). These findings highlight the significant role of transcription factors in regulating the expression of miR‐27a.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, MyoD binds to and activates the miR‐27a‐3p promoter, with binding sites located within the core promoter region (−234/−165 bp) (Tao et al., 2022). Furthermore, c‐Fos was found to promote miR‐27a expression by specifically binding to the miR‐27a promoter region (−983 to −974 region) and subsequently leading to enhance ischemia/reperfusion‐induced myocardial apoptosis in vitro (Bao et al., 2021). These findings highlight the significant role of transcription factors in regulating the expression of miR‐27a.…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 [500], ABCA1 [501], CCR2 [502], LDLR (low density lipoprotein receptor) [503], SIRT1 [504] and NOD2 [505] might crucially contribute to the development of hypercholesterolemia. ABCA1 [506], TLR5 [507], PTGS2 [508], TGFA (transforming growth factor alpha) [509], PDK4 [510], JAK2 [511], TLR2 [512], NEK7 [513], CCR1 [514], BACH1 [515], NCOA4 [195], LATS2 [516], PELI1 [517], EGR1 [518], CYBB (cytochrome b-245 beta chain) [519], MEFV (MEFV innate immuity regulator, pyrin) [520], CLEC4E [521], GCLC (glutamate-cysteine ligase catalytic subunit) [522], KLF3 [523], TP53INP1 [524], ITGB1 [525], IRF9 [526], PHLPP1 [527], NOD2 [528], ACSL4 [529], FGL2 [530], PF4 [531], VEGFB (vascular endothelial growth factor B) [532], CCR7 [533], IGFBP4 [534], TRPM4 [535], BAG1 [536], LGALS3 [537] and ATAD3A [538] could induce ischemic heart disease. Therefore, the data suggest that the identified DEGs which enriched in GO terms and pathways might participant in the development of CAD and its associated complications, and contribute to CAD and CAD related complications treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In various types of cells and stimuli, Fos family members perform different functions, although they have similar structures [ 45 ]. Previous studies have shown that c‐Fos, a member of the Fos family, promotes apoptosis by regulating miR‐27a expression after myocardial I/R injury [ 7 ]. Fra‐1 is a member of the Fos family, with members that dimerize with Jun family members [ 4 ], but the function of Fra‐1 after I/R has been unclear.…”
Section: Disccussionmentioning
confidence: 99%
“…AP-1 transcription factors are signal activated, and they regulate apoptosis and stress responses [5,6]. Increasing evidence has indicated that c-Fos and c-Jun can be induced to high expression levels after ischemia injury and that this upregulation moderates apoptosis [7,8].…”
Section: Introductionmentioning
confidence: 99%